Propasal of possible OTEC sites in Bangladesh - Shakil, Shifur Rahman; Hossain, Md. Safwat; Rouf, Nirjhor Tahmidur (© 2014 IEEE Computer Society, 2017)
This conference paper was presented in the International Conference on Electrical Information and Communication Technology, EICT 2013; Khulna; Bangladesh; 13 February 2014 through 15 February 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/EICT.2014.6777893